Zad 1.wyloncz wspolny czynnik przed znak pierwiastka; √20 +√125 , ³√24,³√32,³√-48,³√1/81.
zad. 3 oblicz sume liczb;√80,√75,³√16,³√24,√20,√72,³√88,³√-297
zad 4.oblicz roznice liczb;√112,√250,√45,√125,³√54,³√-40,³√-50,³√189
zad 7 oblicz; 4√5-10√5+6√5 , 4 ³√2-10 ³√2 + ³√2 + 4 , 10√1/3 +4 √1/3 -11 √1/3 + 3 , -2³√1/5 -10 √1/5 +4 ³√1/5 +3
zad 8.wykona dzialania; √20 +√45 -2√125 , 5³√-81 +5³√-24 + 20 ³√3 ,3√12 -5√27 -10 √48 , 10 ³√2 + ³√-54 -12 ³√-10

2

Odpowiedzi

  • Użytkownik Zadane
2009-10-05T19:01:19+02:00
1.
√20+√125=√(4*5)+√(25*5)=2√5+5√5=7√5
∛24=∛(8*3)=2∛3
∛32=∛8*4=2∛4
∛-48=∛(-8)*6=(-2)∛6
∛(1/81)=∛(1/27)*(1/3)=(1/3)∛(1/3)
3.
√80+√75+³√16+³√24+√20+√72+³√88+³√-297=
√(16*5)+√(25*3)+∛(8*2)+∛(8*3)+√(4*5)+√(9*4*2)+∛(8*11)+∛(27*11)=
4√5+5√3+2∛2+2∛3+2√5+6√2+2∛11+3∛11=
6√5+5√3+2∛2+2∛3+6√2+5∛11
4.
√112-√250-√45-√125-³√54-³√-40-³√-50-³√189=
√(16*7)-√(25*10)-√(9*5)-√(25*5)-∛(27*2)-∛((-8)*5)-∛(-50)-∛(189)=
4√7-5√10-3√5-5√5-3∛2+2∛5+∛50-∛189=
4√7-5√10-8√5-3∛2+2∛5+∛50-∛189
7.
4√5-10√5+6√5 =0
4 ³√2-10 ³√2 + ³√2 + 4 =4-5∛2
10√1/3 +4 √1/3 -11 √1/3 + 3 =3+3√1/3
-2³√1/5 -10 √1/5 +4 ³√1/5 +3=3-8³√1/5
8.
√20 +√45 -2√125 =√(4*5)+√(9*5)-2√(25*5)=2√5+3√5-2*5√5=-5√5
5³√-81 +5³√-24 + 20 ³√3 =5∛((-27)*3)+5∛((-8)*3)+20∛3=-15∛3-10∛3+20∛3=-5∛3
3√12 -5√27 -10 √48 =3√(4*3)-5√(9*3)-10√(16*3)=6√3-15√3-40√3=-49√3
10 ³√2 + ³√-54 -12 ³√-10 =10∛2+∛((-27)*2)-12∛(-10)=
10∛2-3∛2+12∛10=7∛2+12∛10
2009-10-05T20:17:37+02:00

√20+√125=
=√(4*5)+√(25*5)=
=2√5+5√5=
=7√5
∛24=∛(8*3)=2∛3
∛32=∛8*4=2∛4
∛-48=∛(-8)*6=(-2)∛6
∛(1/81)=∛(1/27)*(1/3)=(1/3)∛(1/3)
3.
√80+√75+³√16+³√24+√20+√72+³√88+³√-297=
=√(16*5)+√(25*3)+∛(8*2)+∛(8*3)+√(4*5)+√(9*4*2)+∛(8*11)+∛(27*11)=
=4√5+5√3+2∛2+2∛3+2√5+6√2+2∛11+3∛11=
=6√5+5√3+2∛2+2∛3+6√2+5∛11
4.
√112-√250-√45-√125-³√54-³√-40-³√-50-³√189=
=√(16*7)-√(25*10)-√(9*5)-√(25*5)-∛(27*2)-∛((-8)*5)-∛(-50)-∛(189)=
=4√7-5√10-3√5-5√5-3∛2+2∛5+∛50-∛189=
=4√7-5√10-8√5-3∛2+2∛5+∛50-∛189
7.
4√5-10√5+6√5 =0
4 ³√2-10 ³√2 + ³√2 + 4 =4-5∛2
10√1/3 +4 √1/3 -11 √1/3 + 3 =3+3√1/3
-2³√1/5 -10 √1/5 +4 ³√1/5 +3=3-8³√1/5
8.
√20 +√45 -2√125 =
=√(4*5)+√(9*5)-2√(25*5)=
=2√5+3√5-2*5√5=
=-5√5
5³√-81 +5³√-24 + 20 ³√3 =
=5∛((-27)*3)+5∛((-8)*3)+20∛3=
=-15∛3-10∛3+20∛3=
=-5∛3
3√12 -5√27 -10 √48 =
=3√(4*3)-5√(9*3)-10√(16*3)=
=6√3-15√3-40√3=
=-49√3
10 ³√2 + ³√-54 -12 ³√-10 =
=10∛2+∛((-27)*2)-12∛(-10)=
=10∛2-3∛2+12∛10=
=7∛2+12∛10